Pengaruh Beban Pajak, Intangible Asset, dan Ukuran Perusahaan Terhadap Profit Shifting - Lusyana Dwi Prihatiny, Iris; Irawati, Wiwit (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2023)
This study aims to analyze the effect of tax expense, intangible assets, company size, and profit shifting. This study uses an associative quantitative approach. The population in this study are KOMPAS100 index company for 2017-2021 by taking financial report data on the Indonesia Stock Exchange. The metode of determining the sample used is purposive sampling. The tests used in this study are multiple regression analysis techniques, descriptive statistical test, panel data regression model analysis, selection model tests, multiple linear regression test, and hypothesis test with software eviews version 10. The result showed that there was partially it showed that the tax expense had an negative effect on profit shifting, while intangible assets and company size didn’t have effect on profit shifting.